Burden and predictors of undernourishment among married women of reproductive age: a cross-sectional study in Dadu and Jacobabad districts of the Province Sindh, Pakistan - Zamir Hussain Suhag; Ayaz Ahmed Baloch; Baig, Nelofer; Zohra Lassi; Abdul Wahab Soomro (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the nourishment level of married women of reproductive age in a two rural setting. Method: The cross-sectional study was based on secondary data of the Impact Assessment Survey 2019, which was conducted by the People’s Primary Health Care Initiative from January to May, 2019, in Dadu and Jacobabad districts of the province of Sindh, Pakistan. Nutritional status of married women of reproductive age was analysed using mid-upper arm circumference; <23cm being indicative of under-nourishment, and <21cm of severe under-nourishment. Predicting factors were identified using multivariate logistic regression. Data was analysed using STATA 15. Results: Of 10,388 subjects, 5,138(49.5%) were from Dadu and 5,250(50.5%) from Jacobabad. The overall mean age was 32.9+8.1 with 4,739(45.6%) aged 25-35 years. Overall, 2,336(22.5%) subjects were undernourished and 609(5.9%) were severely undernourished. Age, education, socio-economic status and parity were significant predictors of the nourishment status (p<0.05), while location and health facility type were significant predictors of severe undernourishment (p<0.05), but were not related to undernourishment (p>0.05). Conclusion: Overall nutrition status of the married women of reproductive age in the two rural districts of Sindh was less than satisfactory. Key Words: Undernourishment, Underweight, Mid-upper arm circumference, Women of reproductive age, Pakistan. Continues...